Quality in mathematics teachers training syllabuses (2004)
The purpose of this study is to design instruments to measure the quality of prospective mathematics teachers training plans, within the Spanish context. We conceive the quality of a syllabus as a multidimensional concept that can be articulated by means of dimensions and competences.